1987
DOI: 10.1152/ajprenal.1987.252.3.f517
|View full text |Cite
|
Sign up to set email alerts
|

N-ethoxycarbonyl-2-ethoxy-1,2-dihydroquinoline, amiloride analogues, and renal Na+/H+ antiporter

Abstract: N-ethoxycarbonyl-2-ethoxy-1,2-dihydroquinoline (EEDQ) is a carboxyl-activating agent and has been shown to inhibit the renal Na+/H+ antiporter. The purposes of the present studies were to characterize the kinetics of inhibition of the Na+/H+ antiporter by EEDQ and to determine whether amiloride analogues affect the ability of EEDQ to inhibit the rate of Na+/H+ exchange. Brush-border membrane vesicles (BBMV) were prepared from rabbit kidneys; Na+/H+ exchange rate was assessed by the fluorescence quenching of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
1995
1995

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This result indicates that Na+/H+ exchange is an electroneutral process with a 1:l stoichiometry, and it also precludes the possibility that the H + efflux from the vesicles occurred simply as a response to an inside-positive Nat diffusion potential generated on addition of Na+ to the externa1 medium. Finally, Na+/H+ exchange in M. crystallinum was inhibited by the diuretic drug amiloride, a known inhibitor of the Na+/H+ antiporter in animals and plants (Blumwald and Poole, 1985;Rocco et al, 1987), with a sensitivity similar to that observed for the Na+/H+ antiporter in B. vulgaris (Blumwald and Poole, 1985).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This result indicates that Na+/H+ exchange is an electroneutral process with a 1:l stoichiometry, and it also precludes the possibility that the H + efflux from the vesicles occurred simply as a response to an inside-positive Nat diffusion potential generated on addition of Na+ to the externa1 medium. Finally, Na+/H+ exchange in M. crystallinum was inhibited by the diuretic drug amiloride, a known inhibitor of the Na+/H+ antiporter in animals and plants (Blumwald and Poole, 1985;Rocco et al, 1987), with a sensitivity similar to that observed for the Na+/H+ antiporter in B. vulgaris (Blumwald and Poole, 1985).…”
Section: Discussionmentioning
confidence: 79%
“…These results suggest that the dissipation of the preset pH gradient by Na+ is not due to electrically driven Ht movement through conductive pathways but is consistent with an electroneutral Na+/H+ antiport. The diuretic drug amiloride has been shown to inhibit Na+ uptake via the N a f / H + exchange system in animals rapidly, reversibly, and competitively by binding at or near the Na+-binding site(s) (Rocco et al, 1987). In plants, amiloride has been shown to inhibit competitively the Na+/H+ antiport in Beta vulgaris (Blumwald and Poole, 1985), with a Ki for Na'-dependent H+ fluxes in tonoplast vesicles of 140 WM.…”
Section: Resultsmentioning
confidence: 99%
“…This was obtained when CCCP was added to the incubation medium at two different concentrations. Furthermore, in both presence and absence of CCCP, C1-uptake shows nonsaturable properties, whereas a C1--OH-exchange (CI--H + cotransport) is a saturable mechanism as a Na+-H + exchange (Aronson, Nee & Suhm, 1982;Rocco, Cragoe & Warnock, 1987). The regression lines obtained in Fig.…”
Section: Discussionmentioning
confidence: 77%